(untitled) (Research, Society and Development, 2021)
Objective: To analyze through scientific evidence the occurrence of drug-drug interactions in patients diagnosed with HIV/AIDS. Methodology: This is an integrative review. Data collection took place through the Virtual Health Database held on November 22, 2020. Therefore, the Rayyan application was used to optimize the selection of articles and the synthesis matrix was the method for carrying out the data analysis. Results: It was possible to identify that few studies are carried out with the elderly population that has a diagnosis of HIV/AIDS. Furthermore, it was observed that the main drug interactions occur between antiretrovirals and proton pump inhibitor drugs. Conclusion: The occurrence of drug interactions is frequent in patients diagnosed with HIV/AIDS, especially in the elderly. Therefore, it is essential that further research be carried out on this topic, aiming to formulate strategies to minimize drug-drug interactions and their consequences for the patient.